Human decision change in crowd evacuation: A virtual reality-based study. (1st June 2023) - Zhang, Ming; Xu, Rui; Siu, Ming Fung Francis; Luo, Xiaowei
Abstract: In complex building evacuations, continuous decision-making is unavoidable to make a sequence of route choices at intersections. Evacuees can change their initial decisions with the environmental context changes to deal with the uncertainties of the evacuation. However, this decision-changing phenomenon in evacuation wayfinding has not been well explained. Therefore, this study investigates the decision-changing behavior in crowd evacuation. The influence of two typical crowd flow modes (i.e., symmetric split and asymmetric split crowd flow) on human decision changes in evacuation wayfinding is explored. The results show that evacuees are likely to change their initial route choice decision under the influence of crowd flows, and asymmetric crowd flow significantly reinforces this trend. Moreover, crowd flow modes significantly affected participants' wayfinding performance, including evacuation time, distance, and speed. This study provides behavioral observations and empirical evidence of the persistent effects of crowd flows on evacuees' wayfinding decisions changing and performance during the evacuation. Highlights: The effects of crowd flow modes on decision change behavior are investigated. Evacuees tend to change their initial route choice decision in crowd evacuation. Asymmetric crowd flow significantly reinforces the possibility of decision change. Crowd flow modes significantly affect the evacuation performance of the participant. Crowd flow does not dominate participants' route choices in a single decision.